2014
DOI: 10.1371/journal.pgen.1004871
|View full text |Cite
|
Sign up to set email alerts
|

Vangl2-Regulated Polarisation of Second Heart Field-Derived Cells Is Required for Outflow Tract Lengthening during Cardiac Development

Abstract: Planar cell polarity (PCP) is the mechanism by which cells orient themselves in the plane of an epithelium or during directed cell migration, and is regulated by a highly conserved signalling pathway. Mutations in the PCP gene Vangl2, as well as in other key components of the pathway, cause a spectrum of cardiac outflow tract defects. However, it is unclear why cells within the mesodermal heart tissue require PCP signalling. Using a new conditionally floxed allele we show that Vangl2 is required solely within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 60 publications
4
122
0
Order By: Relevance
“…In the mouse, we and others have carried out tissue-specific gene ablation to demonstrate that PCP genes Dvl1/2 and Vangl2 are required specifically in the SHF lineage for OFT elongation and morphogenesis (Ramsbottom et al, 2014; Sinha et al, 2012). Furthermore, loss of either Wnt5a or Wnt11 also leads to severe conotruncal defects in mice (Schleiffarth et al, 2007; Zhou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, we and others have carried out tissue-specific gene ablation to demonstrate that PCP genes Dvl1/2 and Vangl2 are required specifically in the SHF lineage for OFT elongation and morphogenesis (Ramsbottom et al, 2014; Sinha et al, 2012). Furthermore, loss of either Wnt5a or Wnt11 also leads to severe conotruncal defects in mice (Schleiffarth et al, 2007; Zhou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…CAGG-CreERTM Tg/− mice ( Tg ( CAG-cre/Esr1 )) which constitutively express a transgene encoding tamoxifen-inducible Cre recombinase were bred to Vangl2 flox/flox mice [24] and the CAGG-CreERTM Tg/− Vangl2 flox/+ progeny backcrossed to Vangl2 flox/flox to yield CAGG-CreERTM Tg/− Vangl2 flox/flox conditional knockouts and CAGG-CreERTM Tg/− Vangl2 flox/+ controls. When monolayers of corneal epithelial cells were cultured from these mice, it was found that addition of 10 nM 4-OH tamoxifen to the medium caused nuclear relocalization of the CreERTM within 24 h, knocking out Vangl2 and efficiently removed Vangl2 protein from the cells within 48 h (electronic supplementary material, figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Hemizygous Le-Cre Tg/− mice ( Tg(Pax6-cre,GFP)1Pgr ), driving expression of Cre recombinase in the lens and corneal epithelia [50] and CAGG-CreERTM Tg/− mice ( Tg ( CAG-cre/Esr1 )) driving constitutive expression of tamoxifen-inducible Cre  [51,52] were bred with Vangl2 flox/flox mice [24] and H253 (‘XLacZ’) reporter mice carrying X-linked nLacZ under the control of a housekeeping promoter [30]. Vangl2 Lp/+ mice were as described in [36].…”
Section: Methodsmentioning
confidence: 99%
“…Canonical and non-canonical Wnt signaling pathways can be simultaneously controlled by Syndecan-4, which inhibits canonical Wnt signaling through interaction with LRP6 and R-spondin 3 and activates the non-canonical Wnt pathway (Ohkawara et al, 2011;Astudillo et al, 2014). The importance of non-canonical Wnt signaling for cardiac development has been shown in numerous studies (Phillips et al, 2005;Schleiffarth et al, 2007;Zhou et al, 2007;Ramsbottom et al, 2014). Whether Glypican4 also affects non-canonical Wnt signaling in the anterior LPM is not addressed here.…”
Section: Discussionmentioning
confidence: 99%